Projected changes in mineral soil carbon of European forests, 1990–2100 - Smith, Pete; Smith, Jo; Wattenbach, Martin; Meyer, Jeannette; Lindner, Marcus; Zaehle, Sönke; Hiederer, Roland; Jones, Robert J. A.; Montanarella, Luca; Rounsevell, Mark; Reginster, Isabelle; Kankaanpää, Susanna (Agricultural Institute of Canada, 2006)
Forests are a major land use in Europe, and European forest soils contain about the same amount of carbon as is found in tree biomass. Changes in the size of the forest soil carbon pool could have significant impacts on the European carbon budget. We present the first assessment of future changes in European forest soil organic carbon (SOC) stocks using a dedicated process-based SOC model and state-of-the-art databases of driving variables. Soil carbon change was calculated for Europe using the Rothamsted Carbon model using climate data from four climate models, forced by four Intergovernmental Panel on Climate Change (IPCC) emissions scenarios (SRES). Changes in litter input to the soil due to forest management, projected changes in net primary production (NPP), forest age-class structure, and changes in forest area were taken into account. Results are presented for mineral soil only. Under some climate scenarios carbon in forest soils will increase slightly (0.1 to 4.6 Pg) in Europe over the 21st Century, whilst for one scenario, forest SOC stocks are predicted to decrease by 0.3 Pg. Different trends are seen in different regions. Climate change will tend to speed decomposition, whereas increases in litter input due to increasing NPP and changing age-class structure will slow the loss of SOC. Increases in forest area could further enhance the total soil carbon stock of European forests. Whilst climate change will be a key driver of change in forest soil carbon, changes in ageclass structure and land-use change are estimated to have greater effects.
Keywords: Soil organic carbon; Europe; climate change; forest management; land-use change; Rothamsted Carbon model; EFISCEN model; LPJ model